2021
DOI: 10.3390/ijms22063226
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpene Lactone Deoxyelephantopin Isolated from Elephantopus scaber and Its Derivative DETD-35 Suppress BRAFV600E Mutant Melanoma Lung Metastasis in Mice

Abstract: Melanoma is a highly metastatic disease with an increasing rate of incidence worldwide. It is treatment refractory and has poor clinical prognosis; therefore, the development of new therapeutic agents for metastatic melanoma are urgently required. In this study, we created a lung-seeking A375LM5IF4g/Luc BRAFV600E mutant melanoma cell clone and investigated the bioefficacy of a plant sesquiterpene lactone deoxyelephantopin (DET) and its novel semi-synthetic derivative, DETD-35, in suppressing metastatic A375LM5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…The crystal violet staining cells were quantitatively analyzed and modified according to the study of Cvetannova et al. ( 18 ). The crystal violet-stained cells were then dissolved in 250 μL 20% acetic acid.…”
Section: Methodsmentioning
confidence: 99%
“…The crystal violet staining cells were quantitatively analyzed and modified according to the study of Cvetannova et al. ( 18 ). The crystal violet-stained cells were then dissolved in 250 μL 20% acetic acid.…”
Section: Methodsmentioning
confidence: 99%
“…DET-induced anti-proliferative and pro-apoptotic activities were reversed with the supplementation of GSH (5 µM), which suppressed ROS levels and mitochondrial superoxide generation. Furthermore, DET was found to decrease the basal oxygen consumption rate of A375LM5IF4g/Luc cells by interfering with mitochondrial bioenergetics and inhibiting mitochondrial oxidative phosphorylation [ 81 ]. Similarly, in CNE1 cells, IDET induced ROS generation in a concentration- and time-dependent manner.…”
Section: Effect Of Det and Idet On Apoptosis Pathwaysmentioning
confidence: 99%
“…The mode of action of DETD-35 against cancers is same as that of DET. Several studies have shown that DETD-35 induces ROS-mediated apoptosis through multiple pathways, including Bcl-2 family protein modulation, dissipation of ΔΨm, cell cycle arrest at the G2/M phase, the inhibition of ERK phosphorylation, the induction of autophagy, and the inhibition of metastasis in various cancer cells, including melanoma and triple negative breast cancer cells [ 81 , 115 , 116 , 117 ]. Although DETD-35 has shown promising antitumor activity against melanoma, more comprehensive mechanistic research using in vivo and in vitro studies on different cancer cell models is required to evaluate the real potential of DETD-35 as an anti-cancer agent.…”
Section: Det-derivatives (Detds)mentioning
confidence: 99%
“…Moreover, to establish a metastatic model, human cell lines (e.g., A375 and A2058) can be injected through the i.v. route, usually in the tail vein, and frequently metastasize to the lungs [240][241][242]. Although this procedure allows for rapid spreading of melanoma cells, it does not recapitulate the metastization process that occurs in human disease since, in this case, metastatic cells derive from a primary tumor [90].…”
Section: Xenograft Modelmentioning
confidence: 99%